The GV-LEx corpus of tales in French: Text and speech corpora enriched with lexical, discourse, structural, phonemic and prosodic annotations - Doukhan, David; Rosset, Sophie; Rilliard, Albert; d'Alessandro, Christophe; Adda-Decker, Martine (Language Resources and Evaluation, 2015)
A corpus of French tales is presented. Its two parts, a text corpus and a speech corpus, were designed for studying the relationships between the textual structures of tales and speech prosody, with the targeted application of an expressive text-to-speech synthesis system embedded in a humanoid robot. The 89-tale text corpus, and the 12-tale speech corpus were annotated using a common tale description framework. Lexical level annotations include extended definitions of enumerations, time, place and person named entities, as well as part of speech tags. Supra-lexical level annotations include the segmentation of tales into a sequence of episodes, the localization and attribution of direct quotations, together with tale protagonists co-references. Annotation distributions and inter-annotator agreement were analyzed. The largest coverage and strongest agreement were observed for person named entities, characters' direct quotations, and their associated coreference chains. Speech corpus annotations were extended to allow the analysis of the relations between tale linguistic information and prosodic properties observed in associated speech. Word and phoneme boundaries were inferred through semi-automatic procedures, resulting in linguistic annotations aligned with the speech signal. Intonation stylization models were used to ease the visual and statistical analysis of tale's prosody. Additional meta-information is provided with the speech corpus, allowing describing tale characters according to their gender, age, size, valence and kind. The corpora described in this article are publicly available through the European Language Resources Association catalog.